Corporate social responsibility (CSR) and leadership: validation of a multi-factor framework in the United Kingdom (UK) - Khattak, Shoukat Iqbal; Jiang, Qingquan; Li, Hui; Zhang, Xiaosan (Journal of Business Economics and Management, 2019)
Global surveys indicate that employee engagement costs nearly £70 billion per year in the UK alone with nascent improvement from 2011 to this date. Recognising employee disengagement as a threat to global socio-economic sustainability, experts and scholars offer CSR and employee-centric leadership as practical solutions. Visionary and servant leadership incite superior employee efforts through fair and ethical work values, but past theory and research show limited research on micro-processes that link CSR to employee outcomes. This study tested a value-centered model to examine if the two leadership styles and overall fairness can explain the positive relationship between CSR and extra effort. Data analysis of 512 employee self-reports using the structural equation modelling (SEM), the PROCESS approach and other techniques showed that executive’s CSR values cue to employee visionary and servant leadership, which influence extra effort both directly and indirectly (through overall fairness). Even though employees strongly endorsed the positive influence of universal visionary prototype, overall fairness was more strongly perceived in servant leadership. The paper offers practical implications for organizational theorists and practitioners.